'Pamoja Tunaweza': A Collaborative Program Model for Global Health Training & Education. Issue 1 (26th October 2022) - Moseley, Jeanne; Mboya, Innocent; Haller, Mia; Lasher, Emily; Amour, Caroline; Msuya, Sia; Manongi, Rachel
The past two decades have seen unprecedented student demand for global health education through experiential and engaged learning within institutions of higher education in the United States. This demand created a need for innovative institutional partnerships. Since 2007, faculty from Cornell University's Global Health Program and Kilimanjaro Christian Medical University College (KCMUCo) have worked together to design, implement, and evaluate an innovative experiential learning program in global health and development policy. Since its inception, 176 Cornell undergraduates and 188 KCMUCo medical students have successfully engaged in the policy case study collaborative program and course, leading to the development of 75 policy case studies. This long-term partnership between Cornell and KCMUCo has led to an innovative cross-cultural teaching model, funding support, professional presentations for students and faculty, a visiting scholars program at Cornell, and new avenues for research and collaboration. Fifteen years of sustained partnership has required the navigation of several unique and complex challenges, providing the opportunity to reimagine and strengthen this program and partnership. The objective of this article is to share a powerful program model for global health training and education, and discuss the challenges, successes, and lessons learned through this continued collaboration.